Plant latent defense response to microbial non-pathogenic factors antagonizes compatibility. Issue 8 (10th June 2022) - Yang, Yu; Chen, Shenglan; Wu, Xiaoxuan; Peng, Li; Vílchez, Juan I; Kaushal, Richa; Liu, Xiaomin; Singh, Sunil K; He, Danxia; Yuan, Fengtong; Lv, Suhui; Morcillo, Rafael J L; et al.
Abstract: Unlike microbe-associated molecular patterns (MAMPs) that are readily targeted by host immunity, microbial non-pathogenic factors (NPFs) appear negligible as they do not elicit defense. Little is known about whether and how NPFs may be monitored by hosts to control compatibility. Herein, a forward genetic screening isolated an Arabidopsis mutant with a loss of plant-rhizobacteria mutualism, leading to the disclosure of a plant latent defense response (LDR) to NPFs. The activation of LDR in the mutant, named rol1 for regulator of LDR 1, is triggered by several non-pathogenic volatile organic compounds and antagonizes plant compatibility with the beneficial bacterium Bacillus amyloliquefaciens GB03. The activation of LDR in rol1 is mediated through the prokaryotic pathway of chloroplastic lipid biosynthesis. The rol1 root microbiome showed a reduced proportion of the Bacillaceae family. We propose that, parallel to the forefront immunity to MAMPs, LDR to certain NPFs provides a hidden layer of defense for controlling compatibility with commensal or beneficial microbes. Abstract : Microbial non-pathogenic factors (NPFs) conditionally activate plant latent defense response (LDR) that antagonizes compatibility with beneficial bacteria.